Real-Life Experiences of Students with Disability in Tribhuvan University: Hermeneutic Phenomenological Method - Budhathoki, Mahendra Kumar (Kanya Journal, 2023)
The number of students with disabilities has been increasing nowadays for higher education. Students with disabilities in universities are excluded from the research fields in Nepal although there are some researches done on school children with disabilities and people with disabilities in the family and society: college students with disabilities need to be studied. This study focuses on the lived experiences of students with disabilities while pursuing their studies at Tribhuvan University, Nepal. A hermeneutic phenomenological research method within qualitative approach was applied. A purposive sampling technique was used to select five students with disabilities in this study. The major findings are that the disabled students encountered mainly infrastructure/physical structure barriers, university policy and practice barriers, the university executives’ (un)conscious/ (un)intentional ignorance and attitude barriers while pursuing studies. The students with vision impairment and motor impairment underwent the difficulty with disable-unfriendly physical structures, university policy and practices. The hearing impaired students expressed that the usual class was not for them, and nobody was in the campus for interaction with them. The findings mean the university environments were unfriendly, hostile and adverse to the disabled students. This study may motivate the executives to modify the policy, practices and attitudes toward the disabled.